Newly designed OTS Clip for preventing fully-covered self-expandable metal stent migration in the gastrointestinal tract - Manta, Raffaele; Del Nero, Lorenzo; Todd, Baron; Parodi, Andrea; De Ceglie, Antonella; Zito, Francesco; Pasquale, Luigi; Zullo, Angelo; Conio, Massimo (Endoscopy International Open, 2023)
Background and study aims Fully-covered self-expandable metal stents (FCSEMS) are frequently used for endoscopic management of gastrointestinal lesions. However, stent migration occurs in up to one-third of patients. Different tools are used to anchor stents to prevent migration. A specifically designed over-the-scope device (Stentfix OTS Clip system) was recently introduced to prevent fully covered SEMS migration in the gastrointestinal tract. The study aimed to evaluate technical success and stent migration rates with the Stentfix device.Patients and methods Data were collected from consecutive patients at four participating centers who were at high risk of FCSEMS migration and in whom the anchoring system was used to prevent migration.Results A total of 31 patients were enrolled. Technically successful clip placement was achieved in all cases. At follow-up, the distal part of the device dislocated from the duodenum into the antrum at 3 days in one patient, accounting for a 3.2 % (95 % CI = 0–9.4) rate of stent migration. The underlying lesion being treated healed in all patients, but 10 patients died before stent removal due to neoplastic progression.Conclusions A dedicated over-the-scope stent fixation device appears to be safe and effective in preventing fully-covered SEMS migration through the gastrointestinal tract.